Copper biomachining mechanisms using the newly isolated Acidithiobacillus ferrooxidans B1 - Xenofontos, Eleni; Feidiou, Antri; Constantinou, Marios; Constantinides, Georgios; Vyrides, Ioannis (My University, 2015)
The controlled microbiological corrosion or biomachining has promising applications in the production of microstructures on a metal workpiece. This process is innovative, low cost and environmentally friendly. Acidithiobacillus ferrooxidans B1 was found to be the most effective strain during copper biomachining of a workpiece among 6 isolated A. Ferrooxidans strains. A. ferrooxidans B1 was tested for copper biomachining at various conditions, such as pH regulation (pH 1.8 or unregulated), temperature control (4 °C, 20 °C) and inoculation strategy. The dominant biomachining mechanism was found to be the indirect degradation/bioleaching of copper from the workpiece due to the microbial regenerated ferric ions.
Keywords: Copper; Acidithiobacillus ferrooxidans; Scanning electron microscopy; Biomachining; Roughness